2017
DOI: 10.1590/1414-431x20176297
|View full text |Cite
|
Sign up to set email alerts
|

Revealing potential long non-coding RNA biomarkers in lung adenocarcinoma using long non-coding RNA-mediated competitive endogenous RNA network

Abstract: In our study, we aimed to reveal potential long non-coding RNAs (lncRNA) biomarkers in lung adenocarcinoma (LAD) using lncRNA-mediated competing endogenous RNAs (ceRNAs) network (LMCN). Competing lncRNA-mRNA interactions were identified using the hypergeometric test. Co-expression analysis for the competing lncRNA-mRNA interactions was implemented, and relying on the weight value >0.8, a highly competitive LMCN was further constructed. Degree distribution, betweenness and closeness for LMCN were carried out to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 38 publications
1
23
2
Order By: Relevance
“…We identified some cancer markers by building and analyzing specific or common ceRNA networks [ 9 , 33 , 34 ]. The specific treatment of 2 subtypes of non-small cell lung cancer is a problem that both researchers and clinicians want to solve, but so far there is no good explanation or evidence [ 35 37 ]. We constructed 2 specific networks with mRNA and lncRNA using the specificity of lncRNA to find markers and survival-related genes of 2 different cancers.…”
Section: Discussionmentioning
confidence: 99%
“…We identified some cancer markers by building and analyzing specific or common ceRNA networks [ 9 , 33 , 34 ]. The specific treatment of 2 subtypes of non-small cell lung cancer is a problem that both researchers and clinicians want to solve, but so far there is no good explanation or evidence [ 35 37 ]. We constructed 2 specific networks with mRNA and lncRNA using the specificity of lncRNA to find markers and survival-related genes of 2 different cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The functional roles of LINC00472 in lung cancer have been revealed by bioinformatics analyses. For instance, Sui et al ( 27 ) and Zhu et al ( 28 ) reported that LINC00472 was downregulated in lung cancer by constructing an lncRNA-mediated competitive endogenous RNA network. To the best of our knowledge, the present study was the first to identify that LINC00312 and LINC00472 are associated with smoking-induced lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, researches have demonstrated the significance of ceRNA network during the oncogenesis and progression of various cancers [16][17][18][19]. Some researchers have further identified potential prognostic mRNAs for LADC based on ceRNA network [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%